IMPLEMENTASI ASEAN FRAMEWORK AGREEMENT ON MULTIMODAL TRANSPORT (AFAMT) DI INDONESIA DALAM MENDUKUNG ASEAN CONNECTIVITY PERIODE 2019-2022 - Nabila Putri Herawati (2023)
The high cost of logistics transportation is still a problem that interferes with the creation of ASEAN connectivity. Therefore, it is important for member countries to implement agreements that can overcome these problems, one of which is the ASEAN Framework Agreement on Multimodal Transport (AFAMT) which regulates multimodal transportation. This study aims to determine the Implementation of AFAMT in Indonesia in Supporting ASEAN Connectivity for the 2019-2022 Period. This research uses the theory of compliance, regional cooperation, and multimodal transport using qualitative methods to provide explanations in descriptive form. Researchers found that Indonesia has tried to comply with and implement AFAMT. However, there are still a number of problems, namely that the definition of international multimodal transportation has not been maximized and the implementation of capacity building has not been maximized which makes Indonesia still one of the countries that has not fully complied with AFAMT regulations.